1990
DOI: 10.1111/j.1365-2214.1990.tb00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and antenatal care: the attitudes and experiences of Asian women

Abstract: Asian women living in the East End of London were interviewed in English or in their own language to assess their attitudes to and experiences of pregnancy and antenatal care and to consider some factors which may influence their experiences, especially their fluency in English. In some respects Asian women's experiences were similar to those of non-Asian women reported in other studies, e.g. similar levels of nausea and lack of tie-up between nausea and negative reactions to pregnancy. However there were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…First, language difficulties clearly hamper good communication and understanding between immigrant women and their caregivers when women are not fluent in the language of the receiving country. Communication difficulties were identified as a key problem in almost all the immigrant studies [25-29,32-35,38-45,47-49,51,55]. Lack of information in community languages and insufficient access to interpreters when needed were also commonly reported and a few studies noted that even when interpreters were available, women did not always feel that they were competent [25,45,47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, language difficulties clearly hamper good communication and understanding between immigrant women and their caregivers when women are not fluent in the language of the receiving country. Communication difficulties were identified as a key problem in almost all the immigrant studies [25-29,32-35,38-45,47-49,51,55]. Lack of information in community languages and insufficient access to interpreters when needed were also commonly reported and a few studies noted that even when interpreters were available, women did not always feel that they were competent [25,45,47].…”
Section: Resultsmentioning
confidence: 99%
“…Communication difficulties were identified as a key problem in almost all the immigrant studies [25-29,32-35,38-45,47-49,51,55]. Lack of information in community languages and insufficient access to interpreters when needed were also commonly reported and a few studies noted that even when interpreters were available, women did not always feel that they were competent [25,45,47]. Lack of familiarity with how care is provided or not receiving adequate information about what options for care exist, were also common problems for immigrant women [26,28-32,35-38,41,48,50,51].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Woollett and Dosanjh-Matwala (1990) observed that some midwives held prejudices about minority ethnic women who were perceived to be unable or unwilling to manage their fertility. Women were particularly dissatis®ed with information provided by midwives.…”
Section: Satisfaction With Health Professionals For Somali Womenmentioning
confidence: 94%
“…Interview-based studies from several countries revealed unique rituals surrounding birth, and birth experiences of immigrant women in host countries [1216]. Given the uniqueness of cultures’ birthing experiences, nursing researchers have introduced the subject of culturally competent or transcultural nursing for the nursing curriculum, and also actual programs of culturally competence or transcultural nursing care [17].…”
Section: Introductionmentioning
confidence: 99%